Unearthing Sunken Treasures: Harnessing Underwater Cultural Heritage For Tourism Growth In Galle, Sri Lanka - Suduweli Kondage Lathisha Jayangi Ramanayaka (Politeknik Pariwisata Makassar, 2024)
The allure of delving into ancient, submerged realms has catapulted underwater cultural heritage to prominence within the marine tourism sector. Among the coastal jewels of Sri Lanka, Galle stands out as a city steeped in historical significance, having functioned as a bustling harbour for generations. Beneath its waves lies an underwater museum of artifacts that hold the potential to redefine the tourism landscape of the city. This study ventures into the depths to explore how these sunken treasures could be harnessed to invigorate tourism in Galle. The primary aim is to unravel the role that underwater cultural heritage could play in shaping and enhancing the tourism narrative of Galle City. By evaluating Galle’s capacity to leverage this unique resource, the research seeks to determine how well the city is equipped to cater to this emerging niche and how it can turn its underwater assets into a vibrant tourism draw. To achieve this, the study employs a qualitative research methodology, drawing insights through semi-structured interviews with key stakeholders, including tourism service providers, maritime archaeologists, and museum officials. This approach allows for a nuanced understanding of the existing perceptions and potential of underwater heritage tourism. The data collected were subjected to rigorous content analysis, revealing several critical findings: the substantial underwater cultural heritage assets of the Galle City, the growing interest among tourists in these submerged artifacts, and the current shortcomings in managing and promoting these resources effectively. The findings of the study suggest that an integrated approach—one that intertwines tourism development with the preservation and promotion of underwater heritage—could create a symbiotic relationship. Such a strategy promises to not only enhance the appeal of Galle as a tourist destination but also ensure the sustainable management of its underwater cultural treasures. By fostering this harmony, both the tourism sector and the heritage assets can thrive, enriching the historical and economic landscape of the Galle City